Optical Analysis of 1300 nm GaInNAsSb/GaAs Vertical Cavity Semiconductor Optical Amplifier - Faten Adel Ismael Chaqmaqchee; Shawbo Abdulsamad Abubekr Salh; Mohammed Faeq Mohammed Sabri (Zanco Journal of Pure and Applied Sciences, 2020)
Vertical cavity semiconductor optical amplifiers (VCSOAs) based on GaInNAsSb active region is designed to operate in reflection mode at wavelength of 1300 nm. Addition of antimony Sb to the GaInNAs has dramatically improve the performance of VCSOAs, where the wavelength shifts to longer wavelength. This study is aimed to design GaInNAsSb/GaAs quantum wells (QWs) enclosed between various periods of front and 25-periods of back of AlGaAs/GaAs distributed Bragg mirrors (DBRs) by using MATLAB. GaInNAsSb can be grown and lattice matched to GaAs with a very small band gap and it can be grown monolithically on high quality GaAs/AlGaAs distributed Bragg reflector. Peak reflection gain at around of 53.2 dB at single pass gain of 1.076 is observed. In addition, amplifier bandwidth at various front back mirrors reflectivities is simulated to achieve high gain and wide optical bandwidth at low reflectivity of front mirrors.